The shared variance amongst the measures of individual differences and trait EI: a meta-meta-analytic comparison - Zadorozhny, Bogdan S.; Petrides, K. V.; Yang, Jinyan; van der Linden, Dimitri (Frontiers in Psychology, 2026)
One of the central questions in differential psychology is the extent to which its various aspects are interconnected. Past research has revealed significant correlations amongst widely different constructs including emotional intelligence, the Big Five personality traits, the Dark Triad, cognitive intelligence, and creativity, amongst others. However, few studies have investigated these interrelations concurrently with the aim of constructing a unified model. The present meta-meta-analysis was performed using exclusively meta-analytic correlational data for constructs belonging to the cognitive intelligence, trait and ability emotional intelligence (EI), personality, and miscellaneous factor categories. Relationships amongst these constructs were investigated through a series of Exploratory Factor Analyses, Exploratory Structural Equation Modeling, and Confirmatory Factor Analyses. The results indicate that the latent factor formed by the overlap between the various components of differential psychology is closely linked with trait EI and appears to represent positive psychosocial adjustment or overall well-balanced functioning of the individual.Systematic review registrationhttps://osf.io/8pfwq?view_only=f493ff7aa90145fca6897c258c6099c2.